Assertiveness of Nursing Professionals Working in a University Hospital of Nepal - Shrestha, Romina; Adhikari Mishra, Tulashi; Banstola, Ratna S; Joshi, Sarala (Journal of Institute of Medicine Nepal, 2023)
Introduction To provide patients with appropriate treatment and foster therapeutic interactions, nurses must possess assertiveness. The study objective was to find out the assertiveness of nurses. Methods In this cross-sectional study, 272 nurses were recruited using a proportionate stratified random sampling at Tribhuvan University Teaching Hospital (TUTH), Nepal. Assertiveness was measured with a self-administered questionnaire, 30-item Simple Rathus Assertiveness Schedule. Data analysis was done in SPSS version 16. Independent Sample t-test, Pearson Chi-square test, Fisher’s Exact test, and odds ratio were used to examine the association. Results Among nurses, 192 (70.6%) were assertive with a mean assertiveness score of 18.1±14.7. There was a significant association of nurses’ assertiveness with their marital status (p = 0.02), nursing degree (p=0.03), professional designation (p=0.04), employment type (p= 0.03), and additional training (p=0.004). Nurses with bachelor-level nursing degrees were 1.8 times more assertive (95% CI = 1.05-3.07) than those nurses with certificate-level nursing degrees. Nursing officers were 2.1 times more assertive (95% CI = 1.02 – 4.2) than staff nurses. Further, permanently employed nurses were 2.63 times more assertive (95% CI = 1.35-5.12), and nurses who received additional training were 2.2 times more assertive (95% CI = 1.29-3.83). Conclusion More than two-thirds of nurses working in the university hospital were assertive. Nurses with bachelor-level nursing degrees, with professional designation as “nursing officers”, with permanent employment, and those who received additional training were more assertive. These things should be taken into consideration by the hospital administration to increase assertiveness among nurses.